Advanced material planning performance: a contextual examination and research agenda. Issue 9 (3rd October 2016) - Jonsson, Patrik; Mattsson, Stig-Arne
Abstract : Purpose: The purpose of this paper is to examine the inventory performance effect of advanced material planning modes and analyse how internal and external contextual difficulties moderate this relationship. This study also identifies avenues for future research. Design/methodology/approach: The empirical analysis uses a survey of material planning for purchased items in 292 Swedish manufacturing and wholesaling companies. Three dimensions of inventory performance are dependent variables: material planning performance, inventory turnover rate, and service level. Findings: Advanced material planning modes are directly associated with material planning performance, but this study could not verify direct associations with inventory turnover rate and service-level performances. External and internal contextual difficulties have direct effects on all inventory performance dimensions and moderate the inventory performance effect of advanced material planning modes. The moderating effect is stronger in non-difficult contexts, for which advanced material planning has significant inventory performance effects. Demand- and human-related contextual dimensions are especially critical. Practical implications: The study identifies the following guidelines for companies to consider in order to unlock the potential of advanced material planning: consider full implementation of advanced material planning in non-difficult contexts; minimise the plan variability effects of high parameter revision and planning frequencies; minimise the need for, and use of, manual modification of planned orders before release; reduce demand uncertainty and variability; and secure appropriate human skills and working time. Originality/value: This study somewhat contradicts the literature on material planning by not finding a direct positive effect on any inventory performance dimension from analytical design of order quantities and safety stocks. The research adds to the literature by identifying direct and moderating effects of external and internal contextual difficulties on all three-inventory performance dimensions. The relative importance of managing automatic order release identified in the study motivates future research as the effect has not been previously highlighted in the literature. Accordingly, avenues for future research and an agenda for practice-oriented research are suggested.